The Spirit Of Sobean Kebangkitan Pariwisata Buleleng Di Tengah Pandemi Covid-19 - I Putu Mardika; I Made Bagus Andi Purnomo (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2020)
Tourism in Buleleng is slowly starting to rise amid the Covid-19 pandemic. The revival of tourism in Buleleng after the lull period was carried out with the launch of the concept of The Spirit of Sobean which displays the best local potential in Buleleng. The research analyzed is descriptive qualitative and interpretative, which is through the process of interpreting problems in the field. Next, the data obtained were collected from document studies, photo documentation, field observations, and interviews. This research is also supported by data analysis with qualitative analysis techniques. Furthermore, the researchers conducted studies regarding the policies that the government had taken at the time of the Covid-19 pandemic and its impact on the people in the region. As a result, the mapping of the best local potential in Buleleng to get sobean branding is being carried out by the Pariwsata Service, Culture Service, Trade and Industry Cooperative Service, Agriculture Service and Food Security Service. It is believed that the concept of The Spirit of Sobean will awaken the potential of northern Bali, which has a “nyegara-gunung” geography. This potential is then documented to choose the best. In fact, the Buleleng Tourism Office is targeting 400 new destinations from this Sobean manifestation that were born during this interval. This documentation also maps village profiles covering commodity products, livelihoods, handicrafts, architecture, culture and arts, culinary, loloh and traditional medicine as well as social systems. This is in line with the Law on Cultural Advancement No.5 of 2017, which measures the objects of cultural advancement, namely inventory, security, maintenance, and rescue. Keyword: Sobean, revival of tourism